Effect of zeolitic products in the nutritive quality of the diatom Thalassiosira weissflogii - Arredondo-Vega, Bertha O.; Leal-Lorenzo, Sylvia; López-Ruiz, José (HIDROBIOLÓGICA, 2017)
The marine diatom Thalassiosira weissflogii (Grunow) G. Fryxell et Hasle (= T. fluviatilis Hustedt) was cultured in a batch system with f/2 medium supplemented with 10 mg l-1 of the zeolitic products Zeben 56, Zestec 56 and AZ. After 10 days cell composition was measured. The most important effect was observed with Zestec 56 which induced an increase of octadecatetraenoic acid (C18:4) and docosahexaenoic acid (C22:6 DHA). Results suggest that zeolitic products can be used as part of the f/2 medium to improve the nutritional quality of this diatom.